SOUNDNESS RATING OF BANKS IN INDONESIA PERIOD 2015-2019 - Aldilla Iradianty; Kendra Veren Widya Arista; Hastungkoro Endah Pramesti (Jurnal Media Ekonomi (JURMEK), 2021)
Banks in conducting their business must always pay attention to their soundness by RGEC, Risk Profile, Good Corporate Governance, Earning, Capital to know it belongs to the category of unhealthy, less healthy, fairly healthy, healthy, or very healthy. This study aims to determine bank ratings and to determine whether there are differences in the health condition of banks listed on the Indonesia Stock Exchange in 2015 – 2019 and analyzed based on average composite rankings and one way ANOVA tests to reach comparative conclusions of various RGEC indicator. Based on the risk profile indicator the highest LDR obtained by BJTM and lowest by BBTN, highest NPL obtained by BBCA and the lowest by BEKS, the second indicator is good corporate governance measured using the composite value and the highest obtained by BBCA, NISP, BMRI, BJBR, BJTM, BDMN, BBRI, BBNI and the lowest by BEKS, another indicator is earning measured using NIM, for the highest obtained by BDNM and the lowest by NISP, for ROA the highest obtained by BBCA and the lowest by BEKS, the last indicator is Capital measured using CAR obtained the highest is BJTM and the lowest is BEKS. The ANOVA test results show that there are differences in the health condition of banks in Indonesia for the 2015-2019 period.